(Fremd)Körper Die Stigmatisierung der Neuchristen im Spanien der Frühen Neuzeit - Gebke, Julia (2019)
The ideology of purity-of-blood (limpieza de sangre) divided early modern Iberian society into two different classes: Old Christians and New Christians. New Christians, i.e. Conversos (converted Jews) and Moriscos (converted Muslims), but also their offspring, were thought to be inferior Christians and always tending towards apostasy. At the turn of the 17th century an increased interest in bodily markers to proof the presumed inferiority of the so-called New Christians can be observed. The book focusses on the question how the apologists of the purity-of-blood statutes used the idea of inherited bodily markers to promote a genealogical racism in early modern Iberia.